The Relationship of the Use of Social Media with Premarital Sexual Behavior in Adolescents in SMK Negeri 1, 2019 - Levana Sondakh; Fidyawati Aprianti A. Hiola (Journal of Community Health Provision, 2021)
Premarital sexual behavior can be influenced by the using social media that is not controlled by teenagers. Pornographic content freedom was circulating on social media that triggers negative behaviors in adolescents. The purpose of the research was to determine the relationship of using social media with premarital sexual behavior in adolescents. The method used analytic observational research with cross sectional approach. The results of the research using Chi square test showed that use of social media has a significant relationship with premarital sexual behavior. P value is 0,000 where the value is <0.05 as a significant level.